Neoteric advances in affordable photocatalytic energy conversion and storage with perovskites nanocrystals: A review. (2nd November 2022) - Noor, Asma; Fatima, Nisar; Tahir, Muhammad Bilal; Pervaiz, Muhammad; Tanveer, Muhammad
Summary: Environmental issues caused by energy crisis and its simultaneous demand are the factors driving researchers to explore the studies related to photocatalysis over the globe thus new pathways have come to light in order to store and convert solar energy. However, the conventional materials for the job including metal oxides and sulfides, with the passage of time, are diminishing and are being replaced by their best alternatives such as perovskites and their derivatives. The halide and oxides, with basic composition ABX 3, are most famous among all the perovskites to be used in energy harvesting. The proclaimed supremacy of perovskite photocatalysts with their inherent potential to combat the energy crisis has been the compelling motive for the current article. As nano‐structuring offers manifold features such as porosity, surface area, charge carrier mobility, and confinement. These characteristics contribute to their potential applications in batteries, solar cells, DSSCs, reduction of carbon dioxide, and thermoelectricity. The foregoing literature is devoid of comprehensive discussion on flexile and dynamic nano‐structuring of parovskites concerning CO 2 reduction and thermoelectric utilities. Therefore, perovskites derivatives, mainly halide and oxides have been summarized in the article to provide optimization in energy devices on basis of their structure, morphology, and composition control.